Validation of newly developed culturally specific diabetes self-management education and support program for Iraqi type 2 diabetes mellitus patients - Ehab Mudher Mikhael; Mohamed Azmi Hassali; Saad Abdulrahman Hussain (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Diabetes self-management (DSM) is the cornerstone in diabetes mellitus (DM) management. Unfortunately, the practice of DSM by Iraqi type 2 DM (T2DM) patients is poor that mainly resulted from their poor knowledge about the required DSM behaviors. This lack of knowledge may be attributed to the lack of DSM education and support (DSMES) program in Iraq. Thus, this study was conducted with aim of developing and validating a culturally specific DSMES program for Iraqi T2DM patients. MATERIALS AND METHODS: The development and validation of the DSMES program was done according to the Hilda Taba model. Content validity of the program was done by a panel of 6 health-care experts in management of Iraqi DM patients. Face validity was confirmed by conducting a pilot study for six adults with uncontrolled T2DM at the National Diabetes Center, Baghdad, Iraq. Both the experts and patients were asked to evaluate the developed program in regard to its contents, design, and supporting material (booklet). The evaluation was done by filling in a questionnaire that based on a 5-point scale. Items with a score ≥4 by <70% of the experts and patients were subjected to revision and further assessment. RESULTS: No total disagreement for any item was expressed by all participants (experts and patients). Content and face validity was ensured through obtaining a positive feedback from all participants at which all items about the program had scores of ≥4 by at least 75% of participants. CONCLUSION: The developed culturally based DSMES program is highly suitable for educating Iraqi T2DM patients.